Wideband improvement for hybrid plasmonic fractal patch nanoantenna - Refat Taleb Hussein; Dheif Ibrahem Abood (Institute of Advanced Engineering and Science, 2022)
A wideband improvement for hybrid plasmonic fractal patch nanoantenna is presented for use in intra/inter chip optical interconnects. The suggested fractal patch antenna covering a part of U-band (1625-1675), L-band (1565-1625nm), C-band (1530-¬1565nm), S-band (1460-1530nm), E-band (1360-1460nm) and most of O-band (1260-1360nm) optical communication bands. The proposed antenna has a promising future use in inter and intra chip optical communications to eliminate electrical interconnection limitations such as interconnect density, power consumption and also increasing data rate. The performance of this antenna has been evaluated using full wave simulation computer simulation technology (CST) Microwave software. The impedance bandwidth is largely enhanced by applying rectangular fractal cuts to the both sides of patch. The proposed antenna achieves a wider bandwidth from 168 THz to 228 THz (B.W.=60 THz), which is about 8 times greater the bandwidth of reference antenna with a good gain and more than 95% radiation efficiency throughout the operational bandwidth.